Galatians - Esler, Philip Francis (London ; New York : Routledge, 1998)
Paul's letter to the Galatians, sometimes known as the Magna Carta of Christian liberty, is central to the understanding of the relation of Paul and the Law and is packed with crucial historical, social and theological material. Philip F. Esler provides a detailed and accessible interpretation of the text, which draws on contemporary and modern literary models. He outlines the problems often associated with reading Galatians, the context of the text, the rhetoric of the text and the intercultural and social implications of Galatians. Galatians includes comprehensive indices of anci.
Machine generated contents note: 1. Reading Galatians -- 2. Social identity and the epistle to the Galatians -- 3. Context and rhetoric in Galatians -- 4. problem with mixed table-fellowship -- 5. Paul, Jerusalem and Antioch -- 6. Righteousness as privileged identity -- 7. Paul and the law -- 8. Freedom, the Spirit and community life (Gal. 4.21-6.10) -- Epilogue: the intercultural promise of Galatians -- App. Paul's attitude to the law in Rom. 5.20-21.
Includes bibliographical references (pages 260-275)-and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Bible. -- Social scientific criticism; Bible. -- Criticism, interpretation, etc; Bible; Intercultural communication -- Religious aspects; Group identity; Social Identification; Communication interculturelle -- Aspect religieux; Identité collective; group identity; RELIGION -- Biblical Studies -- New Testament; RELIGION -- Biblical Studies -- Paul's Letters; Social scientific criticism of sacred works; Group identity; Intercultural communication -- Religious aspects; Electronic books; Criticism, interpretation, etc